TINJAUAN PROSEDUR EMERGENCY MESSAGE PADA SOP AFS UNIT ATS REPORTING OFFICE (ARO) DALAM PELAYANAN PENERBANGAN DI PERUM LPPNPI CABANG PONTIANAK - Nella Rosita; Putu Agus Valguna; Lady Silk Moonlight (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Based on Annex 11 Chapter 2 Air Traffic Service it is explained that the ARO Unit is the responsibility of Air Traffic Service (ATS) personnel, which includes Aeronautical Communication Officer (ACO) personnel and Air Traffic Controller (ATC) personnel. In carrying out their profession, ACO personnel are expected to have good work quality in carrying out work in accordance with the procedures listed in the Standard Operational Procedure (SOP) and Letter Coordination Agreement (LOCA). However, the AFS Standard Operational Procedure (SOP) Chapter 6 Contingency Plan point 6.2 which contains Emergency Messages has not been equipped with Emergency Messages procedures. The formulation of the problem in this final project is how to review the procedure for emergency messages in the SOP AFS unit ATS Reporting Office (ARO) Perum LPPNPI Pontianak Branch, with the aim of reviewing the procedure for emergency messages in the SOP AFS unit ATS Reporting Office (ARO) Perum LPPNPI Pontianak Branch. This final project uses a descriptive qualitative research design that uses 2 variables, among others; Giving information (variable Y) and Emergency message Procedure (variable X). Data collection techniques use; observation, interviews, and library studies. Interview were conducted with 6 speakers is Aeronautical Communication personel. From the results of the research that has been done, it can be concluded that the emergency message procedure in the AFS SOP is very much needed in sending emergency news to support flight services, and does not cause errors in sending news. The solution to the problem given is to add an emergency message procedure to the AFS SOP.